The wild ways of conscious will: what we do, how we do it, and why it has meaning - Jordan, J. S. (Frontiers in Psychology, 2013)
It is becoming increasingly mainstream to claim that conscious will is an illusion. This assertion is based on a host of findings that indicate conscious will does not share an efficient-cause relationship with actions. As an alternative, the present paper will propose that conscious will is not about causing actions, but rather, about constraining action systems toward producing outcomes. In addition, it will be proposed that we generate and sustain multiple outcomes simultaneously because the multi-scale dynamics by which we do so are, themselves, self-sustaining. Finally, it will be proposed that self-sustaining dynamics entail meaning (i.e., conscious content) because they naturally and necessarily constitute embodiments of context.